Milky Way's thick and thin disk: Is there a distinct thick disk?. Issue 8 (30th September 2016) - Kawata, D.; Chiappini, C.
Abstract: This article is based on our discussion session on Milky Way models at the 592 WE‐Heraeus Seminar, Reconstructing the Milky Way's History: Spectroscopic Surveys, Asteroseismology and Chemodynamical Models. The discussion focused on the following question: "Are there distinct thick and thin disks?". The answer to this question depends on the definition one adopts for thin and thick disks. The participants of this discussion converged to the idea that there are at least two different types of disks in the Milky Way. However, there are still important open questions on how to best define these two types of disks (chemically, kinematically, geometrically or by age?). The question of what is the origin of the distinct disks remains open. The future Galactic surveys which are highlighted in this conference should help us answering these questions. The almost one‐hour debate involving researchers in the field representing different modelling approaches (Galactic models such as TRILEGAL, Besançon and Galaxia, chemical evolution models, extended distribution functions method, chemodynamics in the cosmological context, and self‐consistent cosmological simulations) illustrated how important is to have all these parallel approaches. All approaches have their advantages and shortcomings (also discussed), and different approaches are useful to address specific points that might help us answering the more general question above.